Imaging findings of gastric plexiform fibromyxoma with a cystic change: A case report and review of literature. Issue 52 (December 2017) - Yang, Min-Xia; Zhao, Zhen-Hua; Yang, Jian-Feng; Chen, Bing; Shen, Xun-Ze; Wei, Jian-Guo; Wang, Bo-Yin
Abstract: Rationale: Plexiform fibromyxoma (PF) is an extremely rare mesenchymal tumor of the stomach, and its radiological findings have not been well described. Here, we analyzed the imaging features of a case of PF. To our knowledge, this is a rare reported case with a remarkable cystic change in the imaging literature. Patient concerns: A previously healthy 50-year-old woman presented with a 1-day history of abdominal pain. Then, she underwent computed tomography (CT) and magnetic resonance imaging (MRI). A cystic-solid well-circumscribed extraluminal mass was located in the posterior wall of the gastric upper body. The solid portion appeared as heterogeneous attenuation/intensity with progressive enhancement while the cystic region had no enhancement. Diagnoses: The potential for malignancy could not be excluded. Interventions: Laparoscopic partial gastric resection was performed. Outcomes: Based on pathological findings, a diagnosis of PF was made. The patient was alive without any recurrence or metastasis of the tumor after 2 years of follow-up. Lessons: As far as we know, a gastric PF with a remarkable cystic change has never been reported. Additionally, the tumor exhibited a progressive enhancement pattern which is a characteristic radiographic feature in our case. Our report may help increase the awareness of this rare but important new disease entity.